2018
DOI: 10.1007/s00384-018-2970-5
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for predicting anastomotic leakage after low anterior resection for rectal cancer

Abstract: Our nomogram was a useful tool for precise prediction of anastomotic leakage after low anterior resection for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 25 publications
1
73
1
7
Order By: Relevance
“…Therefore, patients with type 2 DM should be ensured that blood glucose is well controlled before surgery to reduce the risk of AL. However, several studies found that diabetes was not a risk factor for AL [27, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with type 2 DM should be ensured that blood glucose is well controlled before surgery to reduce the risk of AL. However, several studies found that diabetes was not a risk factor for AL [27, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the multivariate regression analysis, a prediction model was established and presented as a nomogram by using the “rms” package in R software (version 3.4.5; http://www.Rproject.org). Briefly, the nomogram was built as follows: according to the regression coefficients of all independent parameters, scoring criteria were set, and each independent parameter was given a score; then a total score could be calculated for each patient . Finally, the probability of AL in each patient can be calculated with the conversion function between the total score and the probability of AL.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the nomogram was built as follows: according to the regression coefficients of all independent parameters, scoring criteria were set, and each independent parameter was given a score; then a total score could be calculated for each patient. 11,16,17 Finally, the probability of AL in each patient can be calculated with the conversion function between the total score and the probability of AL. Moreover, receiver operating characteristic (ROC) curves and calibration curves were used to assess the discrimination and calibration abilities of the nomogram by using the "rms" and "pROC" packages.…”
Section: Development Of the Prediction Modelmentioning
confidence: 99%
See 2 more Smart Citations